The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Corrigendum: Sea urchins in acute high temperature and low oxygen environments: The regulatory role of microRNAs in response to environmental stress - Lingshu Han; Yanglei Wu; Pengfei Hao; Beichen Ding; Yuanxin Li; Wenpei Wang; Xianglei Zhang; Chuang Gao; Heng Wang; Luo Wang; Weijie Zhang; Yaqing Chang; et al. (Frontiers in Marine Science, 2022)

Sea Urchins in Acute High Temperature and Low Oxygen Environments: The Regulatory Role of microRNAs in Response to Environmental Stress - Lingshu Han; Yanglei Wu; Pengfei Hao; Beichen Ding; Yuanxin Li; Wenpei Wang; Xianglei Zhang; Chuang Gao; Heng Wang; Luo Wang; Weijie Zhang; Yaqing Chang; et al. (Frontiers in Marine Science, 2022)
Strongylocentrotus intermedius is an economically valuable sea urchin species in China. However, its growth and survival are severely constrained by ocean warming and the hypoxia that often accompanies high water temperatures. MicroRNAs (miRNAs) are important regulators of gene expression in response to environmental change. In this study, high-throughput RNA sequencing was used to investigate changes in miRNA expression in S. intermedius under heat (25°C), hypoxia (2 mg/L O 2 ), and combined heat and hypoxia stresses. Twelve small RNAs libraries were constructed and 17, 14, and 23 differentially expressed miRNAs (DEMs) were identified in the heat, hypoxia, and combined stress groups ( P <0.05), respectively. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway functional analyses of putative target genes of the DEMs suggested that these miRNAs were important in basal metabolism, apoptosis, oxidative stress, and immune-related pathways. By co-analysis with published transcriptome data, key DEMs (miR-193, miR-184, miR-133, miR-125, miR-2008) and their key target genes ( EGF3 , ABCB4 , CYCL , PAN2 , CALN ) were identified. Quantitative real-time PCR analysis of the expression of 10 DEMs and their key target genes confirmed the RNA sequencing results. These results provide information on gene expression regulation of the molecular mechanisms underlying the response of S. intermedius to multi-cause environmental stresses.

Transcriptomic and Metabolomic Analyses Provide Insights into the Growth and Development Advantages of Triploid Apostichopus japonicus - Jiahui Xie; Yi Sun; Yue Cao; Lingshu Han; Yuanxin Li; Beichen Ding; Chuang Gao; Pengfei Hao; Xin Jin; Yaqing Chang; Jian Song; Donghong Yin; et al. (Marine Biotechnology, 2022)
Polyploid breeding is widely used in aquaculture as an important area of new research. We have previously grown Apostichopus japonicus triploids with a growth advantage. The body length, body weight, and aestivation time of triploid and diploid A. japonicus were measured in this study, and the transcriptome and metabolome were used to examine the growth advantage of triploids A. japonicus . The results showed that the proportion of triploid A. japonicus with a body length of 6–12 cm and 12–18 cm was significantly higher than that of diploid A. japonicus , and triploid A. japonicus had a shorter aestivation time (39 days) than diploid (63 days). We discovered 3296 differentially expressed genes (DEGs); 13 DEGs (for example, cyclin-dependent kinase 2 ) related to growth advantage, immune regulation, and energy storage were screened as potential candidates. According to Gene Ontology (GO) enrichment analysis, DEGs were significantly enriched in the cytoplasm (cellular component), ATP binding process (molecular function), oxidation–reduction process (biological process), and other pathways. According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment data, DEGs were significantly enriched in ribosome production and other areas. We discovered 414 significant differential metabolites (SDMs), with 11 important SDMs (for example, nocodazole) linked to a growth advantage. SDMs are significantly enriched in metabolic pathways, as well as other pathways, according to the KEGG enrichment results. According to a combined transcriptome and metabolome analysis, 6 DEGs have regulatory relationships with 11 SDMs, which act on 11 metabolic pathways together. Our results further enrich the biological data of triploid A. japonicus and provide useful resources for genetic improvement of this species.

Molecular characterization and expression of the SiUCP2 gene in sea urchin Strongylocentrotus intermedius - Lingshu Han; Zijiao Quan; Bing Han; Beichen Ding; Xiaofang Huang; Heng Wang; Yaqing Chang; Jun Ding (Journal of Oceanology and Limnology, 2021)

Metabolomics analysis for skin ulceration syndrome of Apostichopus japonicus based on UPLC/Q-TOF MS - Yang Zhang; Youquan Wang; Xiaoyu Liu; Beichen Ding; Yi Sun; Yaqing Chang; Jun Ding (Journal of Oceanology and Limnology, 2021)